The Effectiveness of Pocket Book in Increasing Knowledge and Attitude among Mothers as an Effort to Prevent Stunting in the Working Are of Pakem Health Center, Sleman (Study of Mothers with Babies Aged 0-23 Months) - Lina Handayani; Mita Rizky (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Stunting is a growth disorder caused by poor nutrition, repeated infections, and lack of psychosocial encouragement resulting in less than ideal height. According to WHO (2022), Indonesia is the country in South-East Asia with the highest prevalence of 31.0%. The highest stunting cases in Sleman Regency in 2022 were in the Pakem Community Health Center working area at 25.5% per 1000 children under five. Mothers' knowledge and attitudes influence the prevention of stunting, but Pakem Community Health Center has never measured these two things. Health promotion media for preventing stunting by Community Health Centers is still limited in the form of leaflets which only contain material about nutrition for children aged 0 - 24 months, while the pocket book in this study contains nutrition for babies, breastfeeding mothers, and pregnant women. Objective: This research is to determine the effect of pocket book media on increasing mothers' knowledge and attitudes to prevent stunting in the Pakem Sleman Health Center working area. Method: Quasi Experiment research design employed a one group pretest-posttest design with a post-test interval of 7 days from the end of the intervention. The sample consisted of 98 mothers who had children obtained by cluster sampling. The tools used were a pocket book with the title